Neonatal mortality at Leratong Hospital - Moundzika-Kibamba, Jean-Claude (My University, 2016)
Background: Leratong Hospital is a regional hospital in the West Rand of Johannesburg, South Africa. Statistics from maternity in 2008 showed high utilisation rates for delivery services at Leratong but a study on neonatal mortality was not yet done. It was therefore essential to measure and analyse the causes of new-born deaths so as to have policies to advance neonatal care. Objectives: To determine the neonatal mortality rate (NMR), the major neonatal causes of death and the occurrence of avoidable health factors. Methods: This was a prospective review of the clinical records of the 46 neonates who died within the 3 month period (15th April 2013 to the 15th July 2013). Data was obtained from neonatal admission and death registers. Information on the number oflive births was obtained from labour ward registers. Delegation books for nurses were checked to determine the number of nursing staff per shift as well as their allocation in different rooms. Neonate's age, birth weight, gender, race, place of origin, reason for admission and cause of death, were analysed. Health factors examined were access to high care services and to the neonatal ICU, number of staff on duty and the use of treatment guidelines. Questionnaires were used to collect information, and the consent to use clinical records was obtained from the mothers. Descriptive statistics were used to describe the frequencies and percentages of variables. Logistic regression of variables was applied to predict mortality. Results: The overall neonatal mortality rate at Leratong Hospital was lower than the rates found in South Africa and other studies in sub-Saharan Africa. Almost 37% of neonates died within 24 hours of admission. The three most common causes of death were: prematurity (39%), perinatal asphyxia (26%) and infection (20%). More than sixty per cent of deaths occurred in the admission room. Three-quarters of neonates who died (74%) were low birth weight neonates. A critical staff shortage (nurse: neonate rati02.: 1:10) was the most common modifiable factor (63% of deaths). Thirty seven per cent of neonates were denied access to ICU. The significant predictors of neonatal death were being born preterm (OR: 3.1, 95% CI 1.7-6.0), extremely low birth weight (OR: 27.5,95% CI 8.2-92.6), very low birth weight (OR: 5.0, 95% CI 2.1-12.3) and birth by caesarean section (OR: 3.2, 95% CI 1.6-6.2). Conclusions: The study found the neonatal mortality rate at Leratong Hospital in 2013 to be lower than rates recorded in South Africa. Our results showed that the most common causes of neonatal mortality were similar to those in other hospitals in sub-Saharan Africa and in South Africa. A high number of neonatal deaths were avoidable by providing high care services (including NCP AP and surfactant) and adequate number of nurses trained in newborn care in the admission room, improving access to neonatal ICU, early detection of perinatal asphyxia and improved neonatal resuscitation, and the supervision of medical doctors.
A research report is submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Sciences in Child Health Johannesburg, 2016
Keywords: Neonatal mortality; Prematurity; Perinatal asphyxia; Infection; Leratong Hospital